Detecting Bubbles in Hong Kong Residential Property Market - YIU, Matthew S. (Institutional Knowledge at Singapore Management University, 2012)
This study uses a newly developed bubble detection method (Phillips, Shi and Yu, 2011) to identify real estate bubbles in the Hong Kong residential property market. Our empirical results reveal several positive bubbles in the Hong Kong residential property market, including one in 1995, a stronger one in 1997, another one in 2004, and a more recent one in 2008. In addition, the method identifies two negative bubbles in the data, one in 2000 and the other one in 2001. These empirical results continue to be valid for the mass segment and the luxury segment. However, the method finds a bubble in early 2011 in the overall market as well as in the mass segment but not in the luxury segment. This result suggests that the bubble in early 2011 in the Hong Kong real estate market came more strongly from the mass segment under the demand pressure from end‐users of small‐to‐medium sized apartments.